Interactive Multimedia Learning for Vocational Electronics Education: Development, Validation, and Classroom Implementation - Lira Rahma Marzalius; Ilmiyati Rahmy Jasril (Sagamedia Teknologi Nusantara, 2026)
This study presents the design, development, and empirical evaluation of an interactive multimedia learning application for basic electronics instruction in vocational education. To address persistent challenges such as passive learning, limited conceptual understanding, and low learner engagement, the research employed the 4D (Define, Design, Develop, and Disseminate) development model to create a digital learning environment in Adobe Animate. The application integrates dynamic animations, vector-based visualizations, explanatory text, and embedded interactive assessments to support conceptual change and active learning. Content and media validity were assessed through expert evaluations from subject-matter and instructional media specialists, while usability and practicality were examined through field tests involving Grade X students in an Audio-Video Engineering program. The findings show high levels of content accuracy, pedagogical alignment, and interface usability. Practicality results indicate strong learner acceptance, intuitive navigation, and consistent engagement during classroom implementation. Observational and questionnaire data reveal positive effects on students’ learning motivation and participatory behaviors. This study provides empirical evidence of the pedagogical value of interactive multimedia for competency-based technical education and offers a replicable development framework for integrating digital learning media in vocational settings. The findings hold practical and theoretical implications for educators, curriculum designers, and policymakers seeking to improve learning quality in technology-oriented vocational education.